Preparation and characterization of rhodium nanostructures through the evolution of microgalvanic cells and their enhanced electrocatalytic activity for formaldehyde oxidation - Sathe, Bhaskar R.; Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2009)
Shape-controlled morphological evolution of nanostructured Rh has been demonstrated with the help of a galvanic displacement reaction using Al in 1 mM aqueous Rh(III) chloride at an open circuit potential 0.99 V and at a temperature of 273 K (room temperature). Nanospheres composed of small nanoparticles of size around 2.9 +/- 0.4 nm having uniform distribution with a FCC pattern have been evolved during the course of the reaction. Electrochemical results coupled with structural and morphological characterization data from transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), and cyclic voltammetry (CV) suggested the formation of Rh nanostructures. Considering the role of the potential of substrate Al and Rh and diffusion of reactant and product species toward and from the surface of the Al, we proposed the tentative mechanism for the formation of microgalvanic cell. Significantly, these: rhodium nanostructures exhibit enhanced electrocatalytic activity toward many fuel cell reactions as demonstrated by formaldehyde oxidation in 0.5 M NaOH. The present strategy is expected to be valid for preparing many other similar electrocatalysts (Pt, Au, and Pd) capable of exhibiting such a remarkable size- and shape-dependent reactivity.

Electrochemical unzipping of multi-walled carbon nanotubes for facile synthesis of high-quality graphene nanoribbons - Shinde, Dhanraj B.; Debgupta, Joyashish; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of the American Chemical Society, 2011)
Here we report a remarkable transformation of carbon nanotubes (CNTs) to nanoribbons composed of a few layers of graphene by a two-step electrochemical approach. This consists of the oxidation of CNTs at controlled potential, followed by reduction to form graphene nanoribbons (GNRs) having smooth edges and fewer defects, as evidenced by multiple characterization techniques, including Raman spectroscopy, atomic force microscopy, and transmission electron microscopy. This type of ``unzipping'' of CNTs (single-walled, multi-walled) in the presence of an interfacial electric field provides unique advantages with respect to the orientation of CNTs, which might make possible the production of GNRs with controlled widths and fewer defects.

Electrochemical preparation of luminescent graphene quantum dots from multiwalled carbon nanotubes - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemistry-A European Journal, 2012)
Green luminescent, graphene quantum dots (GQDs) with a uniform size of 3, 5, and 8.2(+/- 0.3) nm in diameter were prepared electrochemically from MWCNTs in propylene carbonate by using LiClO4 at 90?degrees C, whereas similar particles of 23(+/- 2) nm were obtained at 30?degrees C under identical conditions. Both these sets of GQDs displayed a remarkable quantum efficiency of 6.3 and 5.1?%, respectively. This method offers a novel strategy to synthesise size-tunable GQDs as evidenced by multiple characterisation techniques like transmission and scanning electron microscopy, atomic force microscopy, Raman spectroscopy and X-ray diffraction (XRD). Photoluminescence of these GQDs can be tailored by size variation through a systematic change in key process parameters, like diameter of carbon nanotube, electric field, concentration of supporting electrolyte and temperature. GQDs are promising candidates for a variety of applications, such as biomarkers, nanoelectronic devices and chemosensors due to their unique features, like high photostability, biocompatibility, nontoxicity and tunable solubility in water.
Keywords: electrochemical synthesis; graphene; Nanostructures; photoluminescence; quantum dots

In situ electrochemical organization of CdSe nanoclusters on graphene during unzipping of carbon nanotubes - Debgupta, Joyashish; Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemical Communications, 2012)
In situ decoration of very small CdSe quantum dots on graphene nanoribbons (GNRs) has been achieved during the electrochemical unzipping of single walled carbon nanotubes. Critical parameters like the width of the GNRs, size distribution of quantum dots and their organization on GNRs have been shown to be strongly dependent on the electric field and time.

Morphology controlled synthesis of LiV(2)0(5)/Ag nanocomposite nanotubes with enhanced electrochemical performance - Diggikar, Rahul S.; Dhavale, Vishal M.; Shinde, Dhanraj B.; Kanbargi, Nihal S.; Kulkarni, Milind V.; Kale, Bharat B. (RSC Advances, 2012)
Uniformly embedded silver (Ag) nanoparticles in orthorhombic nanotubes (NTs) of lithium vanadium oxide (LVO) synthesized via a facile template-free hydrothermal treatment at low temperature exhibited an excellent morphology with good crystallinity and may act as an exceptional contender for electronic applications.

Electrochemical resolution of multiple redox events for graphene quantum dots - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Angewandte Chemie-International Edition, 2013)
Keywords: charging energy; differential pulse voltammetry; graphene; quantum dots; single-electron transfer

Hysteresis and charge trapping in graphene quantum dots - Kalita, Hemen; Harikrishnan, V; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Aslam, Mohammed (Applied Physics Letters, 2013)
We report current hysteresis in response to applied voltage in graphene quantum dots of average diameter 4.5 +/- 0.55 nm, synthesized electrochemically using multiwalled carbon nanotubes. In response to step voltages, transient current decay, characteristic of deep and shallow level charge traps with time constants 186 ms and 6 s, is observed. Discharging current transients indicate charge storage of the order of 100 mu C. Trap states are believed to arise due to the fast physisorption of external adsorbates, which are found to have a significant effect on charge transport and changes the resistance of the prepared device by an order of 3. (C) 2013 American Institute of Physics.

Stabilization of graphene quantum dots (GQDs) by encapsulation inside zeolitic imidazolate framework nanocrystals for photoluminescence tuning - Biswal, Bishnu P.; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Banerjee, Rahul (Nanoscale, 2013)
Luminescent graphene quantum dots (GQDs) are encapsulated and stabilized in Zeolitic Imidazolate Framework (ZIF-8) nanocrystals. The GQDs are well confined due to the adsorption on the growing face of the ZIF-8 nanocrystals and have a profound effect on the shape of the nanocrystals from rhombic dodecahedron to spherical. Stabilizing GQDs inside the ZIF-8 nanocrystals results in tailoring of the photoluminescence emission (ca. 32 nm, bathochromic shift) of the GQD@ZIF-8 nanocrystal composite even after 3 months of aging under normal laboratory conditions. Also the water adsorption (at STP) capacity increased for the GQD@ ZIF-8 composite as compared to the pristine ZIF-8.

Counter-ion dependent, longitudinal unzipping of multi-walled carbon nanotubes to highly conductive and transparent graphene nanoribbons - Shinde, Dhanraj B.; Majumder, Mainak; Pillai, Vijayamohanan K. (Scientific Reports, 2014)
Here we report for the first time, a simple hydrothermal approach for the bulk production of highly conductive and transparent graphene nanoribbons (GNRs) using several counter ions from K2SO4, KNO3, KOH and H2SO4 in aqueous media, where, selective intercalation followed by exfoliation gives highly conducting GNRs with over 80% yield. In these experiments, sulfate and nitrate ions act as a co-intercalant along with potassium ions resulting into exfoliation of multi-walled carbon nanotubes (MWCNTs) in an effective manner. The striking similarity of experimental results in KOH and H2SO4 that demonstrates partially damaged MWCNTs, implies that no individual K+, SO42- ion plays a key role in unwrapping of MWCNTs, rather this process is largely effective in the presence of both cations and anions working in a cooperative manner. The GNRs can be used for preparing conductive 16 k Omega sq(-1), transparent (82%) and flexible thin films using low cost fabrication method.

Mitigating the cytotoxicity of graphene quantum dots and enhancing their applications in bioimaging and drug delivery - Chandra, Anil; Deshpande, Sonal; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Singh, Neetu (ACS Macro Letters, 2014)
Despite the promising photophysical properties of fluorescent graphene quantum dots (GQDs), their cellular toxicity needs to be addressed before their full potential could be completely realized in biomedicine. A simple method for mitigating the toxicity of GQDs by embedding them in PEG matrix is reported here. The enhanced biocompatibility of polymer modified, P-GQDs, is attributed to reduced reactive oxygen species generation, as measured by an intracellular ROS assay. We also demonstrate the enhanced loading and efficient intracellular delivery of therapeutics by P-GQDs.

Sequential electrochemical unzipping of single-walled carbon nanotubes to graphene ribbons revealed by in situ Raman spectroscopy and imaging - John, Robin; Shinde, Dhanraj B.; Liu, Lili; Ding, Feng; Xu, Zhiping; Vijayan, Cherianath; Pillai, Vijayamohanan K.; Pradeep, Thalappil (ACS Nano, 2014)
We report an in situ Raman spectroscopic and microscopic investigation of the electrochemical unzipping of single-walled carbon nanotubes (SWNTs). Observations of the radial breathing modes (RBMs) using Raman spectral mapping reveal that metallic SWNTs are opened up rapidly followed by gradual unzipping of semiconducting SWNTs. Consideration of the resonant Raman scattering theory suggests that two metallic SWNTs with chiralities (10,4) and (12, 0) get unzipped first at a lower electrode potential (036 V) followed by the gradual unzipping of another two metallic tubes, (9, 3) and (10, 1), at a relatively higher potential (1.16 V). The semiconducting SWNTs with chiralities (11, 7) and (12, 5), however, get open up gradually at +/- 1.66 V. A rapid decrease followed by a subsequent gradual decrease in the metallicity of the SWNT ensemble as revealed from a remarkable variation of the peak width of the G band complies well with the variations of RBM. Cyclic voltammetry also gives direct evidence for unzipping in terms of improved capacitance after oxidation followed by more important removal of oxygen functionalities during the reduction step, as reflected in subtle changes of the morphology confirming the formation of graphene nanoribbons. The density functional-based tight binding calculations show additional dependence of chirality and diameter of nanotubes on the epoxide binding energies, which is in agreement with the Raman spectroscopic results and suggests a possible mechanism of unzipping determined by combined effects of the structural characteristics of SWNTs and applied field.
Keywords: density functional-based tight binding calculations; Electrochemistry; graphene; Raman spectral mapping; single-walled carbon nanotubes

Electrochemical preparation of nitrogen-doped graphene quantum dots and their size-dependent electrocatalytic activity for oxygen reduction - Shinde, Dhanraj B.; Dhavale, Vishal M.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Bulletin of Materials Science, 2015)
Here we report a remarkable transformation of nitrogen-doped multiwalled carbon nanotubes (MWCNTs) to size selective nitrogen-doped graphene quantum dots (N-GQDs) by a two-step electrochemical method. The sizes of the N-GQDs strongly depend on the applied anodic potential, moreover increasing potential resulted in a smaller size of N-GQDs. These N-GQDs display many unusual size-dependant optoelectronic (blue emission) and electrocatalytic (oxygen reduction) properties. The presence of N dopants in the carbon framework not only causes faster unzipping of MWCNTs but also provides more low activation energy site for enhancing the electrocatalytic activity for technologically daunting reactions like oxygen reduction. The smaller size of N-GQDs has shown better performance as compared to the large N-GQDs. Interestingly, N-GQDs-3 (size = 2.5 +/- 0.3 nm, onset potential = 0.75 V) show a 30-mV higher positive onset potential shift compared to that of N-GQDs-2 (size = 4.7 +/- 0.3 nm, onset potential = 0.72 V) and 70 mV than that of N-GQDs-1 (size = 7.2 +/- 0.3, onset potential = 0.68 V) for oxygen reduction reaction (ORR) in a liquid phase. These result in the size-dependent electrocatalytic activity of N-GQDs for ORR as illustrated by the smaller sized N-GQDs (2.5 +/- 0.3 nm) undoubtedly promising metal-free electrocatalysts for fuel cell applications.
Keywords: fuel cells; MWCNTs; N-GQDs; oxygen reduction reaction; unzipping

Graphene nanoribbons as prospective field emitter - Khare, Ruchita T.; Shinde, Dhanraj B.; Bansode, Sanjeewani; More, Mahendra A.; Majumder, Mainak; Pillai, Vijayamohanan K.; Late, Dattatray J. (Applied Physics Letters, 2015)
Field emission characteristics of graphene nanoribbons (GNRs) synthesized by unzipping of multiwall carbon nanotubes using a facile hydrothermal route have been investigated at a base pressure of 1 x 10(-8) mbar. The values of turn-on field, required to draw an emission current densities of 1 and 10 mu A/cm(2), are found to be 2.8 and 5.8 V/mu m, respectively, and a maximum emission current density of 500 mu A/cm(2) has been drawn at an applied field of 9.8 V/mu m. The emission current stability of the GNRs emitter was studied at preset values of 1 and 10 mu A over a period of 3 h, and is found to be excellent. The field emission results demonstrated herein suggest that GNRs based field emitters can open up many opportunities for their potential utilization as large area field emitters in various vacuum micro-nanoelectronic devices such as flexible field emission displays, portable X-ray, and microwave tubes. (C) 2015 AIP Publishing LLC.

Synergistic humidity-responsive mechanical motion and proton conductivity in a cationic covalent organic framework - Das, Gobinda; Shinde, Dhanraj B.; Melapurakkal, Amrutha; Shelke, V, Manjusha; Garai, Bikash; Bazin, Philippe; Blal, Abdelhafid Ait; Benyettou, Farah; Prakasam, Thirumurugan; Halim, Rasha Abdul; Ibrahim, Fayrouzabou; Sharma, Sudhir Kumar; et al. (CHEM, 2024)
Keywords: ACTUATORS; Crystalline; DRIVEN; SOFT